2013
DOI: 10.5152/jtgga.2013.81594
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and use of folic acid among reproductive age and pregnant women

Abstract: It is thought that there is a relatively high incidence of NTD in Turkey, which is due to inadequate information about NTDs and the use of folic acid. Primarily health care professionals such as midwives, nurses and family physicians should aim to inform all reproductive age women about folic acid for the prevention of NTDs, who should be encouraged to take the supplement when planning pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 25 publications
3
24
0
3
Order By: Relevance
“…Research from Romania revealed that above average nutritional knowledge was a strong determinant of folic acid, iron and multivitamins supplementation in pregnancy [6]. Similar to our results, other studies observed that women with higher incomes used supplementation more often [4,7,27,28]. This fact is not a surprise, as most of supplements are not subsidized, therefore they can be a substantial financial burden on a family's budget.…”
Section: Source Of Knowledge About Proper Nutrition During Pregnancysupporting
confidence: 88%
See 3 more Smart Citations
“…Research from Romania revealed that above average nutritional knowledge was a strong determinant of folic acid, iron and multivitamins supplementation in pregnancy [6]. Similar to our results, other studies observed that women with higher incomes used supplementation more often [4,7,27,28]. This fact is not a surprise, as most of supplements are not subsidized, therefore they can be a substantial financial burden on a family's budget.…”
Section: Source Of Knowledge About Proper Nutrition During Pregnancysupporting
confidence: 88%
“…National data has shown that the use of supplements are still neglected [2,3]. Other studies carried out in various countries worldwide clearly demonstrate that mistakes in diet and supplementation are a global health problem [4][5][6][7][8]. There are many factors that may have impact on the decision to take supplements during pregnancy, among them socio-economic status, place of residence and level of education are often highlighted [4][5][6][7]9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, commercially available vitamin tablets with folic acid are prescribed for pregnant women. Folic acid is available in different doses in multivitamin tablets or in tablets only containing folic acid [9]. It has been reported that folic acid absorption rate is 100% from multivitamin supplements [10].…”
Section: Introductionmentioning
confidence: 99%